Financial Performance: An Early Abandoned or Independently Sufficient Approach. (A Systematic Literature Review) - Ait Jillali, Sanae; Belkasseh, Mohammed (Archives of Business Research, 2022)
The organizational performance is a central subject of management sciences since it occupies an axial position in the control and steering mechanisms. Several researchers have tried to explore it and fix it by relying on certain concepts that are easy to grasp, including effectiveness and efficiency. Furthermore, dissecting it by dimensions according to approaches such as; the goal achievement model, the resource acquisition model, and theories like; the stakeholder theory. In the literature, the financial approach was most advocated for judging and measuring the success of any business. Besides, many authors have affirmed that with the development and inseparability of social, economic, and environmental factors, the financial aspect becomes insufficient and abandoned. It is in this perspective that the present paper, by being part of a series of works seeking to clarify the contours of organizational performance, aims to provide answers to the problem of the relative importance given to financial indicators and their reliability for the evaluation and measurement of performance in different contexts. Based on literature and main models of performance, we tried to collect then analyze a set of theoretical and empirical articles likely to better display the perception of financial performance by the organization and its shareholders, as well as the role of this dimension in translating the financial success (using purely economic PIs) or global prowess (leaning on extra-financial PIs) of companies regardless of their structure. Knowing that the performance doesn’t have the same meanings depending on features and many factors specific to the company.